Impediments to the use of educational technology in physical education lesson for the schools of education Baghdad - Karkh / 1 - Mohammed, Abdul Salam (Journal of Physical Education, 2010)
The present study aims at clarifying the state of utilizing educational technology in general education in BAGHDAD. It also attempts to shed some light on the difficulties faced in using such technology. Data were obtained from various previous studies relating to the subject, from interviews with a number of school principals. A questionnaire was also administered to a random of sample of 31 sport teachers from Al-kaarch/ 1 Educational Area and 60 male and female students from two schools in the same area. The findings of the study were as follows:1.Teachers were aware of the importance of the constant use of educational technology. Nevertheless, their responses to some items relating to the use of modern educational technology were discouraging, which should be taken into consideration in establishing a training programme for teachers.2.Lack of training courses for teachers, especially courses that teach them how to produce and develop their teaching materials. This has led to a greater difficulty for teachers who tried to utilize educational technology. That was the most formidable problem for them because lack of training leads to all sorts of difficulties that were observed in the present study. It can be the source of more difficulties if it is not encountered and dealt with properly.3.The students’ awareness of the importance of educational technology is increasing. Yet the researcher aspires for more than that through providing educational technology and teaching aids in schools for students to benefit from them in the educational process. They will doubtless overcome the difficulties that face them in learning their school subjects